A caged 2‐hydroxyethyl luciferin for bioluminescence imaging of nitroxyl in living cells. (30th June 2020) - Ju, Yong; Wang, Anni; Li, Xuewei; Xu, Xu; Lu, Jianzhong
Abstract: Nitroxyl (HNO), a one‐electron reduction product of nitric oxide, demonstrates distinct biological and pharmacological activities. Here we designed a bioluminescent turn‐on probe, HNO‐8, that could be used to visualize HNO without the need for excitation light. HNO‐8 was prepared by caging 2‐hydroxyethyl luciferin with a triphenylphosphine unit, in which 2‐hydroxyethyl luciferin as a novel substrate of firefly luciferase was characterized by stronger and more sustained bioluminescent signals than the most popular substrates of d ‐luciferin and 6′‐aminoluciferin. In vitro experiments showed that HNO‐8 could selectively respond to HNO generated from Angeli's salt(AS) in the range 1–50 μM, with a limit of detection of 0.196 μM. The probe was successfully applied for visualizing HNO in luciferase‐transfected Huh7 cancer cells. We envision that HNO‐8 could be used as a powerful bioluminescent sensor for researching HNO biological roles.